Analysis Of The Application Of Recording Methods And Assessment Of Inventories In Accordance With Psak No. 14 At Andrew Smith Urban Lifestyle Supermall Karawaci - Dwi Kartinah; Tommy Kuncara (Publisher Cv. Inara, 2021)
Inventory is one of the assets that has an important role for the activities of a company. The problem that often occurs in inventory is when recording and evaluating inventory. Generally, recording is not detailed or even manually, thus making inventory reports unclear and not good. This makes the researcher want to compare the inventory treatment of Andrew Smith's Urban Lifestyle Supermall Karawaci store with PSAK No. 14.This research was conducted using a descriptive method with quantitative and qualitative data sourced from primary and secondary data. The data obtained are then processed, analyzed, and interpreted to determine the comparison with PSAK No. 14. Andrew Smith Urban Lifestyle is a manufacturing company engaged in the men's clothing industry such as: jackets, shirts, pants, chinos, sweaters, blazers, ties, accessories, shoes, and sneakers. The result of this research is that the store's inventory recording has not used a method that is in accordance with PSAK No. 14, there is only a partial recording referring to the perpetual method, namely when there is an entry and exit of goods that is directly recorded in a computerized manner. While the inventory valuation is also not in accordance with PSAK no. 14 because it does not use the FIFO method. Using the FIFO method will result in a clearer and better inventory valuation.